2011
DOI: 10.1007/s00414-011-0642-x
|View full text |Cite
|
Sign up to set email alerts
|

Mutation rate estimates for 13 STR loci in a large population from Rio Grande do Sul, Southern Brazil

Abstract: Short tandem repeat (STR) polymorphisms have been extensively used in forensic genetics analysis. Knowledge about the locus-specific mutation rates of STRs improves forensic probability calculations and interpretations of diversity data. To incorporate single-locus diversity information into autosomal STR mutation rate estimations, 13 STR loci were studied during 2007-2009 in 10,959 paternity investigation cases from Rio Grande do Sul, the southernmost state of Brazil, covering an overall number of 284,934 all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 3 publications
5
9
1
1
Order By: Relevance
“…Based on the number of meiosis per locus, the overall mutation rate determined in this study for the 15 forensic STR loci was 1.3 × 10 −3 (95% CI: 1.1–1.5 × 10 −3 ), which is a similar value to the findings of previous studies with Brazilian populations of the Southern and Southeastern regions , and with Polish and Southern Chinese Han populations, which ranged from 1,18 × 10 −3 to 1,39 × 10 −3 . The mutation rate calculated in this study is, however, slightly different from an earlier study including Southern, Southeastern and Central Brazilian populations (0.94 × 10 −3 ) and data published for the Northeastern region of the country (0.75 × 10 −3 ) , and much higher than the rate reported in a recent study analyzing a population from Central Brazil (0.21 × 10 −3 ) .…”
Section: Slippage Mutations Observed In 5171 Paternity Cases From Indsupporting
confidence: 87%
See 2 more Smart Citations
“…Based on the number of meiosis per locus, the overall mutation rate determined in this study for the 15 forensic STR loci was 1.3 × 10 −3 (95% CI: 1.1–1.5 × 10 −3 ), which is a similar value to the findings of previous studies with Brazilian populations of the Southern and Southeastern regions , and with Polish and Southern Chinese Han populations, which ranged from 1,18 × 10 −3 to 1,39 × 10 −3 . The mutation rate calculated in this study is, however, slightly different from an earlier study including Southern, Southeastern and Central Brazilian populations (0.94 × 10 −3 ) and data published for the Northeastern region of the country (0.75 × 10 −3 ) , and much higher than the rate reported in a recent study analyzing a population from Central Brazil (0.21 × 10 −3 ) .…”
Section: Slippage Mutations Observed In 5171 Paternity Cases From Indsupporting
confidence: 87%
“…We observed the highest STR mutation rates at loci vWA (2.8 × 10 −3 ), FGA and D18S51 (both with 2.7 × 10 −3 ), while loci TH01 and TPOX had no mutations. In previous studies performed in Southern and Central Brazil populations, vWA, FGA, and D18S51 were also the loci presenting the highest mutation rates, while TH01 and TPOX also presented very low mutation rates. Two other studies, one performed in a population from São Paulo and another one in Poland , reported the highest rates for vWA and FGA, with D12S391 and D5S818, being the third highest mutated loci, respectively.…”
Section: Slippage Mutations Observed In 5171 Paternity Cases From Indmentioning
confidence: 68%
See 1 more Smart Citation
“…Investigations of genetic links using database DNA has stood out in recent years (Chung and Fung, 2013;Mardini et al, 2013). Moreover, the study of human race has been of interest since ancient times.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, considerable research has been conducted to identify the geographical origin of people and their closeness, from several points of view, as well as the degree of admixture in the genetic composition of a population. Therefore, the aim of this study was to determine the allele frequencies and haplotype diversity of Y-STRs in the population of Goias State, Central Brazil, and to compare the results with population data for samples from all Brazil regions (Mardini et al, 2013). …”
Section: Introductionmentioning
confidence: 99%